Effects of occupational health and safety management systems implementation in accident prevention at a Harare beverage company - Tatenda Musungwa; Pedzisai Kowe (Taylor and Francis Group, 2022)
Occupational health and safety management (OHSMS) systems are recognised internationally as highly flexible and can be tailored to all sizes and types of businesses to manage accidents, injuries, fatalities and health risks at workplaces. This study evaluated the effectiveness of OHSMS audits to occupational accidents mitigation in food and beverage industries at Delta Sparkling Beverages, Harare, Zimbabwe. The study was based on an analytical research using a combination of qualitative and quantitative techniques. In particular in-depth interviews, non-participatory observations and documentary records data search were utilised. 84 questionnaires were self-administered to Delta Sparkling Beverages, employees from different departments using a stratified random technique in 2020. The effectiveness of OHS audits were analysed in which purposive interviews were employed to solicit vital information from key experts in the field of study. The study also sought to highlight challenges faced in the operationalisation of OHSMS audits and the implementation of safety systems. Statistical Package for Social Sciences (SPSS) was used for quantitative data analysis. The results of chi-square (p > 0.05) indicated that there was no association between occurrence of accidents at Delta Sparkling Beverages to OHSMS audits. The research findings further revealed that non-adherence to safe operating procedures (unsafe acts) by employees is the major cause of accidents at the company. The study recommended intervention towards employee behaviour, safety proceduresand ways to improve safety culture within the company.